Long-term X-Ray Variability on the Benchmark YSO HL Tau - Steven M. Silverberg; Scott J. Wolk; David A. Principe; P. C. Schneider; Hans Moritz Günther; Jinyoung Serena Kim; Joel H. Kastner (The Astronomical Journal)
HL Tau is one of the most well-studied Class I young stellar objects (YSOs), including frequent observations at near- and mid-infrared, (sub)millimeter, and X-ray wavelengths. We present the results of an X-ray variability monitoring campaign with XMM-Newton in 2020 and X-ray grating spectroscopy from Chandra/HETGS in 2018. We find that the X-ray spectrum of HL Tau is consistently hot (with characteristic plasma temperatures T  ≳ 30 MK) over 31 epochs spanning 20 yr, which is consistent in temperature with most Class I YSOs. The high-resolution HETG spectrum indicates the presence of some cooler plasma. We characterize the variability of the star across the 31 observations and find a subset of observations with significant variability on a ∼21-day timescale in the observed count rate and flux. We discuss the possible origins of this variability and identify further observations that would better constrain the nature of the changes.